Design and Development of Medical Image Processing Experiment System Based on IDL Language - Xie, Wei (Bioautomation, 2019)
This paper uses Interactive Data Language (IDL) as a development language to design and implement a lung tumor image processing system with a Client/Server (C/S) structure. During the development process, various business requirements related to the system have been analyzed and the system structure together with detailed business process were designed as a whole. In addition, we also established a database of patients’ lung tumor images to efficiently store and query Computed Tomography (CT) images of lung tumors at various stages of the patient and the images generated during the processing of the system. Finally, the paper elaborated the implementation of the IDL-based lung tumor image processing system, and conducted a performance test and experimental analysis of the system. The system consists of five functional modules: image preprocessing, image segmentation, image reconstruction, image measurement, and image management. This system can automatically calculate quantitative indicators in the delineated area. These features can be used for further tumor differentiation tests, tumor characterization, treatment monitoring, and prognosis assessment. The experimental results show that the system is effective, and also processing speed meets the real-time requirements, and has wide applicability, friendly human-computer interaction, convenient extensibility, good portability, and so on.